Consumer acceptance of an iron bean variety in Northwest Guatemala: The role of information and repeated messaging - Salomón Pérez; Adewale Oparinde; Ekin Birol; Carolina González; Manfred Zeller (Agricultural and Food Economics, 2018)
Micronutrient malnutrition affects 2 billion people worldwide and biofortification could prove to be a cost-effective solution to its alleviation. The aims of this study are as follows: (i) to understand consumer acceptance of the main sensory characteristics such as taste, color, texture, etc., of an iron-enriched bean variety compared to a popular traditional one ('parramos'); (ii) to measure consumer willingness to pay (WTP) for an iron-enriched bean variety compared to a traditional one; (iii) to investigate the role of nutrition information; and (iv) to understand the impact of information repetition on consumer acceptance. To achieve this, a home use testing (HUT) method and a Becker-DeGroot-Marshak mechanism were used. The results indicate that consumers equally preferred the iron-enriched and the local bean varieties, although some minor differences were found in some of the sensory characteristics. Although the mean WTP for the iron-enriched bean variety was higher, the difference was not statistically significant among the groups evaluated. The information provided and the order of variety delivery play a significant role in consumer acceptance for the iron-enriched variety, and repetition in providing information had a positive impact depending on the type of message provided and on who received it (e.g., men or women, more educated respondents). Potential censored bids were found due to the nature of the currency interval and some transaction costs.
Keywords: 330; Consumer acceptance; Willingness to pay; Iron-enriched bean; Nutritional information; Guatemala